Analisis Hukum Terhadap Perlindungan Tenaga Kerja - Muhammad Mahmud; Rahmad (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2021)
This study aims to determine labor protection according to Islamic law and positive legal labor protection and the comparison of labor protection according to Islamic law and positive law. This research uses the library research method (library research), meaning that the collection of data or materials needed in writing this thesis comes from books, and review the documentation. Analysis of data using descriptive analysis, namely interpreting data that has been verified and declared in accordance with the research. The results showed that, Islam acknowledges the fact that property is jointly produced by labor and capital. Islam has established several rules to protect their rights. Comparison of labor protection according to Islamic law and positive law. Islam recognizes the fact that property is jointly produced by labor and capital. Therefore, the labor force has a position that is comparatively weaker than the employer, Islam has stipulated several rules to protect their rights whereas in positive law, protection of workers is intended to guarantee workers' rights and guarantee equal opportunity and treatment in the absence of any. discrimination against anything to realize the welfare of workers and their families while still paying attention to developments in the progress of the business world and the interests of entrepreneurs.